A specific electrochemiluminescence sensor for selective and ultra-sensitive mercury(ii) detection based on dithiothreitol functionalized copper nanocluster/carbon nitride nanocomposites. Issue 14 (19th June 2019) - Liu, Huitao; Gao, Xueqing; Zhuang, Xuming; Tian, Chunyuan; Wang, Zhenguang; Li, Yanxiu; Rogach, Andrey L.
Abstract : A novel electrochemiluminescence sensor based on the combination of copper nanoclusters and carbon nitride nanosheets was fabricated for detecting Hg 2+ . Abstract : Electrochemiluminescence (ECL) sensors are useful for the detection of heavy metal pollutants, in particular mercury(ii ) ions, in water samples. We demonstrate the superior sensing performance of Hg 2+ using a nanocomposite material based on carbon nitride nanosheets (CNNSs) and copper nanoclusters functionalized by dithiothreitol, which not only stabilizes the clusters, but also improves the sensitivity of Hg 2+ detection. The ECL mechanism is related to the reaction of the nanocomposite with K2 S2 O8 in the electrochemical system, while the presence of Hg 2+ leads to quenching of its excited state, and the suppression of the formation of anion-radicals. The Hg(ii ) sensor presented here is cheap and fast, and shows high selectivity for the detection of Hg 2+ on the background of other mono-, di-, and trivalent ions, with a linear range of 0.5–10 nM and the detection limit as low as 0.01 nM.